Social Media Tools for TV Programmes Promotion - Kitsa, Mariana; Mudra, Iryna (Communication Today, 2018)
Social media are an important opportunity for communication and an efficient media promotion tool. Intelligent use of social media tools to promote media content helps to increase site traffic, build mass media image, and increase its reach. Today, the majority of young and adult viewers of the ‘traditional’ television get information from the social media first. According to our previous surveys, social media are the source, from which modern society get the information in the first place, and only after a working day watch TV to get the full picture of affairs. That is why, it is very important for “television” in the traditional meaning of this word to popularise itself through the social media. The most efficient methods of TV promotion via social media are personalisation, hosting news on social media, posting video, audio and photo materials, live broadcasting, direct communication with social network readers (users), etc. It is also very important to popularise both a TV channel’s website and programming. Every year social networks are becoming more and more popular with businessmen and media managers alike. Managers of the most popular TV channels have already appreciated the positive trends of using social networks because social media promotion tools help to boost TV programmes’ recognition and the audiences’ awareness of them.